2011
DOI: 10.1029/2010jg001463
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal contributions of vegetation types to suburban evapotranspiration

Abstract: [1] Evapotranspiration is an important term of energy and water budgets in urban areas and is responsible for multiple ecosystem services provided by urban vegetation. The spatial heterogeneity of urban surface types with different seasonal water use patterns (e.g., trees and turfgrass lawns) complicates efforts to predict and manage urban evapotranspiration rates, necessitating a surface type, or component-based, approach. In a suburban neighborhood of Minneapolis-Saint Paul, Minnesota, United States, we simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 94 publications
(166 reference statements)
4
77
0
Order By: Relevance
“…For comparison, summertime daily evapotranspiration rates from UK woodlands are around 4-5 mm day −1 (Roberts et al, 2005;Thomas et al, 2011). Evapotranspiration rates from residential and recreational areas in suburban MinneapolisSaint Paul, Minnesota are around 3 mm day −1 in summer (Peters et al, 2011), comparable to the BLS-MWS results shown here, but near zero in winter (conditions are much colder and drier). The Swindon results are thus comparable to other published findings, but to obtain concurrent Q H and Q E at this scale is rare.…”
Section: Comparison With Other Sitessupporting
confidence: 70%
“…For comparison, summertime daily evapotranspiration rates from UK woodlands are around 4-5 mm day −1 (Roberts et al, 2005;Thomas et al, 2011). Evapotranspiration rates from residential and recreational areas in suburban MinneapolisSaint Paul, Minnesota are around 3 mm day −1 in summer (Peters et al, 2011), comparable to the BLS-MWS results shown here, but near zero in winter (conditions are much colder and drier). The Swindon results are thus comparable to other published findings, but to obtain concurrent Q H and Q E at this scale is rare.…”
Section: Comparison With Other Sitessupporting
confidence: 70%
“…12). The proportion of evergreen trees around the measurement tower is small, so this is most likely due to grass growth in early spring, occurring before leaf-out of deciduous trees (Peters et al, 2011). Warmer temperatures in the urban environment can also encourage early onset of the growing season compared to rural areas (Zhang et al, 2004).…”
Section: Carbon Fluxmentioning
confidence: 99%
“…At the same time, hot summers lead to boreal forest decline (Joos et al 2001;Lucht et al 2006). Moreover, deciduous forests and herbaceous biomes are characterized by a lower evapotranspiration compared to evergreen forests (Zhang et al 2001;Peters et al 2013).…”
Section: Annual Discharge At Watershed Outletmentioning
confidence: 99%